Miteinander für morgen Für Arbeitszeiten, die zum Leben passen - Hofmann, Jörg; Schaumburg, Stefan; Smolenski, Tanja (Edition Politik, 2019)
The IG Metall has put the topic of working time on the agenda: for more self-determination for the employees. In this book, actors present the course and outcome of the 2018 collective bargaining round in the metalworking and electronics industries and take a look at key elements of trade union action. Justice, autonomy, solidarity and power are at the center. They see the collective bargaining round as a practical prelude to a future debate on the role of trade unions, participation and participation in a society in transition.